KUALITAS PELAPORAN KEUANGAN: BERBAGAI FAKTOR PENENTU DAN KONSEKUENSI EKONOMIS - Fanani, Zaenal (Jurnal Akuntansi dan Keuangan Indonesia, 2009)
The research aimed to discuss the determining factors and the economic consequences o f financial reporting quality in Indonesian capital market. Those determining factors are innate, performance, company risk and industry risk. The financial reporting quality was measured on the following attributes: relevance, timeliness, and conservatism, whereas the economic consequence was measured on the asymmetric information. The research employed three steps o f test: (1) test whether the attributes o f financial reporting quality are different with each other; (2) analyze the determining factors offinancial reporting quality; (3) test the effect o f financial reporting quality in the stock market, in terms o f the relationship between asymmetric information and the financial reporting quality. The result o f the first test showed that all o f the attributes o f financial reporting quality are different with each other. The analysis o f determining factors showed that sales volatility, firm performance, and classification o f the industry had a significant relationship with the attributes o f financial reporting quality. The other variables, such as operation cycle, firm size, company risk, liquidity, and leverage, had no significant relationship with the attributes o f financial reporting quality. The economic consequence test resulted that the attributes o f financial reporting quality had a significant relationship with the asymmetric information.